PENGARUH PENERAPAN STRATEGI PEMBELAJARAN KOLABORATIF FISHBOWL TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS VII SMP NEGERI 6 RENGAT - Sri Yunita Ningsih; Nurseha Nurseha (Universitas Islam Sumatera Utara, 2018)
Abstract. The research is motivated by the low ability of problem solving in student math SMP Negeri 6 Rengat, the activity of students in following the lesson is still relatively low. The us of fishbowl collaborative learning strategy is throught to be able overcome the problem solving ability of student math which is still low. The purpose of this research is to know the ability of problem solving of student mathematics by using fishbowl collaborative learning strategy. This type of research is experimental research. The research design used was randomized subjects posttest only control group design. The population in these villages is class VII. The class selected to be the experimental class is the class VIIA and the control class is the class VIIB. The data collection technique used in this research is the ability problem solving test in the form of essay. Data analysis techniques in this test use t test based on hypothesis test results obtained t count = -4,321 and t table = -2,010. Based on hypothesis test results t arithmetic t table with the real level used is 0,05. Ho rejected. So, it can be concluded that the ability to solve mathematical problem with the application of fishbowl collaborative learning strategy is better than the ability to solve mathematical problems with the application of conventional learning strategies in the class VII SMP Negeri 6 Rengat. Keywords: Collaborative Learning Strategy Fishbowl, Problem Solving